1984
DOI: 10.1099/0022-1317-65-8-1385
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Interference Between Influenza A/WSN and B/Kanagawa Viruses

Abstract: SUMMARYSimultaneous infection of MDCK cells with influenza viruses A/WSN and B/Kanagawa resulted in mutual interference with virus protein synthesis and in significant suppression of A/WSN growth. When infection by one virus preceded the other by 1 or 2 h, growth of the superinfecting virus was selectively inhibited at the level of transcription. Interference by the pre-infecting virus was strongly dependent on the expression of the viral genome but not on haemagglutinin activity. When the replication of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…To demonstrate the interference of IAV mediated by IBV, Wantichang et al co-infected cells with DsRed-expressing sciIAV ΔNA and either of two IBV strains (B/Lee/40 and B/Maryland/2/59) (Wanitchang et al, 2012). In agreement with previous studies (Aoki et al, 1984), the authors used flow cytometry to show that DsRed expression was markedly lower in IBV, but not IAV (WT PR8) co-infected cells (Wanitchang et al, 2012). Cells that overexpressed IBV NP prior to sciIAV ΔNA infection were refractory to high DsRed expression post-infection, demonstrating that IBV NP was sufficient to interfere with IAV replication.…”
Section: Sciiav Applicationssupporting
confidence: 82%
See 1 more Smart Citation
“…To demonstrate the interference of IAV mediated by IBV, Wantichang et al co-infected cells with DsRed-expressing sciIAV ΔNA and either of two IBV strains (B/Lee/40 and B/Maryland/2/59) (Wanitchang et al, 2012). In agreement with previous studies (Aoki et al, 1984), the authors used flow cytometry to show that DsRed expression was markedly lower in IBV, but not IAV (WT PR8) co-infected cells (Wanitchang et al, 2012). Cells that overexpressed IBV NP prior to sciIAV ΔNA infection were refractory to high DsRed expression post-infection, demonstrating that IBV NP was sufficient to interfere with IAV replication.…”
Section: Sciiav Applicationssupporting
confidence: 82%
“…In fact, a competitive interference at the level of viral transcription between both virus species has been reported (Aoki et al, 1984; Gotlieb and Hirst, 1954; Kaverin et al, 1983). To demonstrate the interference of IAV mediated by IBV, Wantichang et al co-infected cells with DsRed-expressing sciIAV ΔNA and either of two IBV strains (B/Lee/40 and B/Maryland/2/59) (Wanitchang et al, 2012).…”
Section: Sciiav Applicationsmentioning
confidence: 99%
“…Several reports have indicated that, upon co-infection of cells in vitro, IBV impairs the replication of IAV, a phenomenon called intertypic or heterotypic interference (Tobita and Ohori, 1979;Mikheeva and Ghendon, 1982;Kaverin et al, 1983;Aoki et al, 1984). Mechanistically, it has been shown that the NP of IBV (NP B ) can inhibit IAV polymerase activity through binding to its type A counterpart (NP A ) thus disrupting interaction between NP A and PB2, preventing IAV polymerase complex formation and ultimately leading to the growth suppression of co-infecting IAV (Wanitchang et al, 2012;Jaru-ampornpan et al, 2014;Narkpuk et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies so far have focused on IBV interference on IAV replication, and have suggested that IAV interference on IBV infection was less pronounced (Tobita and Ohori, 1979;Mikheeva and Ghendon, 1982;Kaverin et al, 1983;Aoki et al, 1984). Here, in order to gain further insight into the mutual interference between IAV and IBV, we developed an original system using recombinant viruses harboring a fluorescent reporter in co-infection experiments and analyzed the outcome using flow cytometry on infected cells.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, mixed infection between two types of plant tospoviruses results in interspecies interaction between their N proteins and more severe symptoms compared to single infections, suggesting synergy between these viruses (Bag et al, 2012;Tripathi et al, 2015). On the other hand, intertypic interference between types A and B influenza viruses could be partially explained by the inhibitory effect of type B influenza virus nucleoprotein exerted on its type A counterpart (Aoki et al, 1984;Jaru-ampornpan et al, 2014). Given structural similarities, we expect that CoV N proteins would likely cross-interact with each other during a co-infection event.…”
Section: Introductionmentioning
confidence: 99%